Genetics and Genomics of the Triticeae - Feuillet, Catherine; Muehlbauer, Gary J. (Plant Genetics and Genomics: Crops and Models, 2009)
Genetics and Genomics of Triticeae Edited by Catherine Feuillet and Gary Muehlbauer Domestication of cereals in the Fertile Crescent 10,000 years ago ushered in the beginning of agriculture, and signified a remarkable breakthrough in the advancement of civilization. Today, the crops of the Triticeae tribe, wheat, barley, and rye, constitute over 50% of total crop production worldwide (http://www.fao.org/) and cereal seeds are one of the most important renewable resources for food, feed, and industrial raw materials. The economic importance of the Triticeae has triggered intense cytogenetic and genetic studies over the past few decades, and has resulted in a breadth of information and tools for developing wheat, barley, and rye varieties. Hampered by the size and complexity of their genomes, however, research regarding the genomics of the Triticeae has lagged behind. But, the recent convergence of several technology developments has enabled dramatic breakthroughs in genomic research and led to the development of a robust "Genomic toolbox." These new capabilities permit a better understanding of the biology of the Triticeae plants and support the improvement of agronomically important traits in these essential species. Comprised of the work of internationally recognized experts, Genetics and Genomics of Triticeae provides an in depth summary of the advances of the past decades, synthesizes the current state of knowledge of the structure, function, and evolution of the Triticeae genomes, and describes progress in the application of this knowledge to the improvement of wheat, barley, and rye. This book explores both the fundamentals of genetic and genomic research of the Triticeae and the applications of state of the art technology that have led to improvements in agronomically important traits such as biotic and abiotic stress resistance, plant development, and quality. Genetics and Genomics of Triticeae opens perspectives into the deployment of new genetic approaches to identify traits and create a better understanding of the organization of the Triticeae genome, and the ongoing development of new sequencing technologies that will support future genome sequencing of these essential crops. Catherine Feuillet is research director and leader of the group "Structure, function and evolution of the wheat genomes" at the INRA, Clermont-Ferrand (France). She was educated as a geneticist and molecular biologist and worked for 10 years in Switzerland on the genomics of disease resistance in wheat and barley before moving to France. She is one of the co-chairs of the International Wheat Genome Sequencing Consortium (IWGSC), the International Triticeae Mapping Initiative (ITMI), and the European Triticeae Genomics Initiative (ETGI). Gary J. Muehlbauer is an Associate Professor and Endowed Chair in Molecular Genetics of Crop Improvement in the Department of Agronomy and Plant Genetics at the University of Minnesota. He studied maize genetics during his Ph.D. at the University of Minnesota and his postdoctoral work at the University of California at Berkeley. He has been on the faculty at the University of Minnesota for eleven years working on barley and wheat genomics. He is the vice chair of the International Barley Sequencing Consortium.